Peningkatan Hasil Belajar Kognitif dengan Menggunakan Model Pembelajaran Kooperatif Tipe Group Investigation (GI) Pada Siswa Kelas X MIA SMAS NW Mataram Tahun Pelajaran 2018/2019 - Pertiwi, Dian Esti; Muliadi, Agus; Samsuri, Taufik (Jurnal Ilmiah IKIP Mataram, 2020)
The purpose of this study was to improve students cognitive learning outcomes through Cooperative Group Investigation learning model in 10th grade student MIA 2 of NW Mataram senior high school 2018/2019. The subjects of this study were 10th grade student MIA 2 of NW Mataram senior high school 2018/2019. This is a classroom action research (CAR) using two cycles. The instruments used in this study were lesson plan observation sheets (RPP) and student cognitive learning outcomes test sheets as many as 20 multiple choice questions and 5 essay questions. The results in the first cycle of the first meeting reached 63.63% with good categories and at the second meeting reached 88.8% with very good categories, while for students’ cognitive learning outcomes in the first cycle obtained an average value of 59 with the classical completeness reached 46% with category is not complete. Meanwhile, in the second cycle at the first meeting of learning implementation (RPP) reached 72.72% with a good category and at the second meeting reached 94.44% with a very good category and for cognitive learning outcomes students in the second cycle obtained an average value of 72 with a classical completeness achieved 76%. Thus, it can be concluded that the results of this study indicate an increase in the cognitive learning outcomes of 10th grade students through cooperative learning model type Group Investigation in MIA 2 NW Mataram 2018/2019.